2020
DOI: 10.1111/codi.15423
|View full text |Cite
|
Sign up to set email alerts
|

Survey to define informational needs of patients undergoing surgery for Crohn’s anal fistula

Abstract: Aim There are many surgical treatments used in Crohn's anal fistula, although none is perfect. Decisions about surgery in this condition may be preference sensitive. The aim of this study was to identify what information patients would like in order to make treatment decisions and to explore experiences of making decisions in this setting. Method A survey was designed based upon qualitative interviews and input from patients and clinicians. It included a long list of informational items to be ranked on a scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…Decision regret was low but comparable to other areas of IBD [29], surgery [30] and the wider literature [31]. There was no difference in regret between the medicine and surgery group.…”
Section: Discussionsupporting
confidence: 74%
“…Decision regret was low but comparable to other areas of IBD [29], surgery [30] and the wider literature [31]. There was no difference in regret between the medicine and surgery group.…”
Section: Discussionsupporting
confidence: 74%
“… 21 Another survey-based study identified wound and aftercare, effect on perianal symptoms, and severity of surgery (risks of procedure, procedure-related pain, and invasiveness) as information needs of patients undergoing surgery for CPF. 22 Participants in a qualitative exploration of patient CPF experiences reported that physicians often did not explain goals and methods of treatment coherently or provide realistic expectations about setons and pain following surgery. 17 …”
Section: Discussionmentioning
confidence: 99%
“…In discrete choice studies, designed to understand factors influencing decisions, patients frequently weight avoidance of severe complications as the first or second most important factor in treatment decisions, rather than achieving cure or remission [10,11]. Survey work has shown that patients are keen to improve perianal symptoms, have limited need for wound care and hospital reattendance, and minimal surgery [12].…”
mentioning
confidence: 99%